The Effect Of Organic Liquid Fertilizer On 5 Paddy Gogo Varieties (Oryza sativa L.) In The Sub-Optimal Land Of Wamena - Sumiyati Tuhuteru; Anti Uni Mahanani; Rio Ginting; Patras Pumoko (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2021)
Paddy gogo is one type of non-irrigated paddy that can grow on limited inputs, one of which is the problem of water availability. Paddy gogo can grow on various types of soil, including sub-optimal land in Wamena. It is said to be sub-optimal considering the ability of the soil in the study area is a type of soil with very low nutrient content. This study aims to determine the effect of the use of NASA organic liquid fertilizer on the growth and yield of 5 varieties of upland rice plants that were tested in the sub-optimal land of Wamena. This research was conducted in March-August 2019. The study was arranged in factorial research design, namely 5 types of varieties as factor 1 (variety of Inpago Unsoed 1, Inpago Unsoed Parimas, Inpari 28, Inpago 9 and one type of Local varieties as Comparator) and the concentration of NASA liquid organic fertilizer as a second factor (150 ml/plot). The results showed that the best growth was shown by varieties Local of Wamena (Moai) with the highest appearance of plant height and Inpago Unsoed 1 varieties which showed a large number of producing offspring. When viewed from physiological and production parameters, Inpago 9 variety shows the highest leaf area index and grain weight per clump. Furthermore, Wamena Local variety showed the highest value of stomata density, Inpago Unsoed Parimas variety showed the highest total chlorophyll value and Inpago Inpari 28 variety was the producer of the highest weight value of 1000 seeds.Keywords: Liquid Organic Fertilizer; Paddy Gogo; Sub-optimal land